Restricting carbohydrates at breakfast is sufficient to reduce 24-hour exposure to postprandial hyperglycemia and improve glycemic variability - Chang, Courtney R (Am J Clin Nutr, 2019)
BACKGROUND: The breakfast meal often results in the largest postprandial hyperglycemic excursion in people with type 2 diabetes. OBJECTIVE: Our purpose was to investigate whether restricting carbohydrates at breakfast would be a simple and feasible strategy to reduce daily exposure to postprandial hyperglycemia. DESIGN: Adults with physician-diagnosed type 2 diabetes [n = 23; mean ± SD age: 59 ± 11 y; glycated hemoglobin: 6.7% ± 0.6%; body mass index (kg/m(2)): 31 ± 7] completed two 24-h isocaloric intervention periods in a random order. Participants consumed one of the following breakfasts: 1) a very-low-carbohydrate high-fat breakfast (LCBF; <10% of energy from carbohydrate, 85% of energy from fat, 15% of energy from protein) or 2) a breakfast with dietary guidelines–recommended nutrient profile (GLBF; 55% of energy from carbohydrate, 30% of energy from fat, 15% of energy from protein), with the same lunch and dinner provided. Continuous glucose monitoring was used to assess postprandial glucose responses over 24 h, and visual analog scales were used to assess ratings of hunger and fullness. RESULTS: The LCBF significantly reduced postprandial hyperglycemia after breakfast (P < 0.01) and did not adversely affect glycemia after lunch or dinner. As such, overall postprandial hyperglycemia (24-h incremental area under the glucose curve) and glycemic variability (mean amplitude of glycemic excursions) were reduced with the LCBF (24-h incremental area under the glucose curve: −173 ± 361 mmol/L; P = 0.03; mean amplitude of glycemic excursions: −0.4 ± 0.8 mmol/L · 24 h; P = 0.03) compared with the GLBF. Premeal hunger was lower before dinner with the LCBF than with the GLBF (P-interaction = 0.03). CONCLUSIONS: A very-low-carbohydrate high-fat breakfast lowers postbreakfast glucose excursions. The effects of this simple strategy appear to be sufficient to lower overall exposure to postprandial hyperglycemia and improve glycemic variability. Longer-term interventions are warranted. This trial was registered at clinicaltrials.gov as NCT02982330.